Does a Satisfied Customer Care about Price? The Link between Customer Satisfaction and Price Sensitivity in the Commercial Martial Arts Industry. Issue 3 (3rd July 2019) - Ouyang, Lei; Hungenberg, Eric; Gray, Dianna
ABSTRACT: Extensive research has shown that customer satisfaction is an important driver of profitability. However, academic understanding of pricing outcomes associated with customer satisfaction evaluations is limited. The purpose of this study was to investigate the relationship between customer satisfaction and price sensitivity, while also examining the moderating effects of gender and participation frequency. Results indicated that four dimensions of customer satisfaction have an inverse effect on customer price sensitivity. Results also showed that there were significant differences on the linkage between customer satisfaction and price sensitivity across gender and participation frequency groups. These findings illuminate concerns among martial arts consumers which are most likely to prompt an exploration of alternative purchase choices in attempt to seek fairer pricing. They also identify individual characteristics among martial arts segments which can be used to build pricing strategy.